2011
DOI: 10.1073/pnas.1018157108
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput ectopic expression screen for tamoxifen resistance identifies an atypical kinase that blocks autophagy

Abstract: Resistance to tamoxifen in breast cancer patients is a serious therapeutic problem and major efforts are underway to understand underlying mechanisms. Resistance can be either intrinsic or acquired. We derived a series of subcloned MCF7 cell lines that were either highly sensitive or naturally resistant to tamoxifen and studied the factors that lead to drug resistance. Gene-expression studies revealed a signature of 67 genes that differentially respond to tamoxifen in sensitive vs. resistant subclones, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 36 publications
4
82
0
Order By: Relevance
“…The screen identified 15 genes, including RAD21, that when overexpressed led to antiestrogen resistance. A study that compared the gene expression profiles of MCF7 cells with acquired resistance to tamoxifen showed a significant increase in RAD21 expression (and a 3-fold decrease in PDS5B expression) in tamoxifen-resistant versus tamoxifen-sensitive cells (138). These studies are consistent with the idea that increased cohesin activity leads to resistance to selective ER modulators.…”
Section: Cohesin May Modify Chromatin In Response To Steroid Hormonessupporting
confidence: 74%
“…The screen identified 15 genes, including RAD21, that when overexpressed led to antiestrogen resistance. A study that compared the gene expression profiles of MCF7 cells with acquired resistance to tamoxifen showed a significant increase in RAD21 expression (and a 3-fold decrease in PDS5B expression) in tamoxifen-resistant versus tamoxifen-sensitive cells (138). These studies are consistent with the idea that increased cohesin activity leads to resistance to selective ER modulators.…”
Section: Cohesin May Modify Chromatin In Response To Steroid Hormonessupporting
confidence: 74%
“…To validate this hypothesis, 2 datasets, GSE33366 10 and GSE26459, 11 were Figure 2. Elevated expression of the turquoise ME, a group of coexpressed genes indicates poor outcome in ERC breast cancer patients treated with tamoxifen.…”
Section: Identification Of Hub Genes That May Participate In Tamoxifementioning
confidence: 99%
“…Some papers demonstrate that autophagy is required for tamoxifen resistance (Qadir et al, 2008;Samaddar et al, 2008;Cook et al, 2012), i.e., autophagy protects breast cancer cells; however, another study examining tamoxifen resistance mechanisms (also in MCF7 cells) performed a high throughput screen for kinases that confer resistance to tamoxifen in sensitive MCF7 cells. This identified a kinase called HSPB8 and showed that its ability to protect against tamoxifeninduced death was associated with its ability to induce autophagy (Gonzalez-Malerva et al, 2011). The conclusion from this latter study was that tamoxifen resistance could be overcome by increasing autophagy.…”
Section: Effects Of Autophagy On Cancer Therapy: Both Positive and Nementioning
confidence: 50%